A novel combined anorectal biofeedback and percutaneous tibial nerve stimulation protocol for treating fecal incontinence. (June 2020) - Mazor, Yoav; Prott, Gillian M.; Sequeira, Carol; Jones, Michael; Ejova, Anastasia; Kellow, John E.; Schnitzler, Margaret; Malcolm, Allison
Background/Aims: Fecal incontinence (FI) is a common, debilitating condition that causes major impact on quality of life for those affected. Non-surgical treatment options include anorectal biofeedback therapy (BF) and percutaneous tibial nerve stimulation (PTNS), usually performed separately. The aims of the current study were to determine the feasibility, tolerability, safety, and efficacy of performing a combined BF and PTNS treatment protocol. Methods: Female patients with urge FI were offered a novel pilot program combining BF with PTNS. The treatment protocol consisted of 13 weekly sessions: an educational session, followed by 5 combined BF and PTNS sessions, 6 PTNS and a final combined session. Anorectal physiology and clinical outcomes were assessed throughout the program. For efficacy, patients were compared with BF only historical FI patients matched for age, parity, and severity of symptoms. Results: A total of 12/13 (93%) patients completed the full program. Overall attendance rate was 93% (157/169 sessions). Patient comfort score with treatment was rated high at 9.8/10 (SD 0.7) for PTNS and 8.6/10 (SD 1.7) for the BF component. No major side effects were reported. A reduction of at least 50% in FI episodes/week was achieved by 58% of patients by visit 6, and 92% by visit 13. No physiology changes were evident immediately following PTNS compared with before, but pressure during sustained anal squeeze improved by the end of the treatment course. Comparing outcomes with historical matched controls, reductions in weekly FI episodes were more pronounced in the BF only group at visit 6, but not week 13. Conclusions: In this pilot study, concurrent PTNS and anorectal biofeedback therapy has been shown to be feasible, comfortable, and low risk. The combined protocol is likely to be an effective treatment for FI, but future research could focus on optimizing patient selection.